Variable Neighborhood Search based algorithms for high school timetabling. - Fonseca, George Henrique Godim da (2015)
This work presents the application of Variable Neighborhood Search (VNS) based algorithms to the High School Timetabling Problem. The addressed model of the problem was proposed by the Third International Timetabling Competition (ITC2011), which released many instances from educational institutions around the world and attracted 17 competitors. Some of the VNS algorithm variants were able to outperform the winner of Third I T C solver, which proposed a Simulated Annealing – Iterated local Search approach. This result coupled with another reports in the literature points that VNS based algorithms are a practical solution method for providing high quality solutions for some hard timetabling problems. Moreover they are easy to implement with few parameters to adjust.